2016
DOI: 10.3171/2015.5.peds14728
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth and alignment after occipitocervical and atlantoaxial fusion with rigid internal fixation in young children

Abstract: OBJECT The long-term consequences of atlantoaxial (AA) and occipitocervical (OC) fusion and instrumentation in young children are unknown. Anecdotal reports have raised concerns regarding altered growth and alignment of the cervical spine after surgical intervention. The purpose of this study was to determine the long-term effects of these surgeries on the growth and alignment of the maturing spine. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…Eighteen patients (21%) from 1 study underwent a combined OC wiring and screw-rod construct [12]. Fourteen (16%) from 2 studies underwent an unspecified form of OC screw-rod construct, including occipital screws and C1–2 transarticular instrumentation, C1 lateral mass and C2 pars screws, and occipital and C2 pars screws alone [13]. Seven patients (8%) underwent an OCF with C1–2 transarticular screw placement only.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen patients (21%) from 1 study underwent a combined OC wiring and screw-rod construct [12]. Fourteen (16%) from 2 studies underwent an unspecified form of OC screw-rod construct, including occipital screws and C1–2 transarticular instrumentation, C1 lateral mass and C2 pars screws, and occipital and C2 pars screws alone [13]. Seven patients (8%) underwent an OCF with C1–2 transarticular screw placement only.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding cervical alignment, a previous study demonstrated that most young children undergoing upper cervical fusion continue to have good alignment and continued growth within the fused levels after surgery 24) . In the present study, O-C2 and C2-7 angles were maintained and C2-7 ROM was surprisingly increased at final follow-up, which might be a result of the specific population of syndromic patients with ligamentous laxity.…”
Section: Fusion Rates and Complications Related To Fusion Surgery In mentioning
confidence: 99%
“…The fusion rate is reportedly as high as 95% and long-term follow up revealed preserved cervical lordosis in 85% of young children who underwent CVJ rigid internal fixation. 27,32) Interestingly, even after rigid internal fixation, the fixed occipitocervical and atlantoaxial distances increase in close to half and nearly all children treated, respectively. 32) …”
Section: Introductionmentioning
confidence: 99%
“…27,32) Interestingly, even after rigid internal fixation, the fixed occipitocervical and atlantoaxial distances increase in close to half and nearly all children treated, respectively. 32) …”
Section: Introductionmentioning
confidence: 99%